2022
DOI: 10.1080/07853890.2022.2069852
|View full text |Cite
|
Sign up to set email alerts
|

Examining longitudinal disparities in COVID-19 prevalence in the U.S.: a county level growth rate perspective

Abstract: Background: The objectives of the present study are to understand the longitudinal variability in COVID-19 reported cases at the county level and to associate the observed rates of infection with the adoption and lifting of stay-home orders. Materials and Methods: The study uses the trajectory of the pandemic in a county and controls for social and economic risk factors, physical environment, and health behaviors to elucidate the social determinants contributing to the observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Third, there were limits to the frequency of observations recorded in the field for this study. More recent public health and real estate research papers are beginning to fill this gap by examining impacts over longer periods of time (Lee et al, 2021;Carozzi et al, 2022;Guo et al, 2023;Kiaghadi et al, 2022;Motoyama, 2022;Wang et al, 2022a;Wu et al, 2022;Tsou et al, 2023). Fourth, as a study of urban neighborhoods, zoned for growth, in a US city, at the center of a metropolitan area, there are limits to the generalizability of this work and its findings.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there were limits to the frequency of observations recorded in the field for this study. More recent public health and real estate research papers are beginning to fill this gap by examining impacts over longer periods of time (Lee et al, 2021;Carozzi et al, 2022;Guo et al, 2023;Kiaghadi et al, 2022;Motoyama, 2022;Wang et al, 2022a;Wu et al, 2022;Tsou et al, 2023). Fourth, as a study of urban neighborhoods, zoned for growth, in a US city, at the center of a metropolitan area, there are limits to the generalizability of this work and its findings.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization [ 39 ] reported that social equity issues need to be addressed amidst COVID-19 because vulnerable groups are hit harder in terms of infection and mental health. The underdeveloped level of medicine, backward housing environment and shortage of community services in small cities are not conducive to treatment and follow-up rehabilitation for COVID-19 [ 40 ]. Therefore, it is significant and urgent to study the public emotional response to the pandemic in small cities.…”
Section: Introductionmentioning
confidence: 99%